Effect of surgical treatment on the cellular immune response of gastric cancer patients - Barbieri,C. (2003)
Patients with gastric cancer have a variety of immunological abnormalities. In the present study the lymphocytes and their subsets were determined in the peripheral blood of patients with gastric cancer (N = 41) both before and after surgical treatment. The percent of helper/inducer CD4 T cells (43.6 ± 8.9) was not different after tumor resection (43.6 ± 8.2). The percent of the cytotoxic CD8+ T cell population decreased significantly, whether patients were treated surgically (27.2 ± 5.8%, N = 20) or not (27.3 ± 7.3%, N = 20) compared to individuals with inflammatory disease (30.9 ± 7.5%) or to healthy individuals (33.2 ± 7.6%). The CD4/CD8 ratio consequently increased in the group of cancer patients. The peripheral blood lymphocytes of gastric cancer patients showed reduced responsiveness to mitogens. The defective blastogenic response of the lymphocytes was not associated with the production of transforming growth factor beta (TGF-ß) since the patients with cancer had reduced production of TGF-ß1 (269 ± 239 pg/ml, N = 20) in comparison to the normal individuals (884 ± 175 pg/ml, N = 20). These results indicate that the immune response of gastric cancer patients was not significantly modified by surgical treatment when evaluated four weeks after surgery and that the immunosuppression observed was not due to an increase in TGF-ß1 production by peripheral leukocytes.